Developing and validating a holistic welfare assessment tool for zoo-housed great apes: Integrating resource-based measures with behavioural ecology insights - Johanna Neufuss; Kirsten Pullen; Holly L. Farmer; Cerian Tatchley; Nick Davis; Jackie Chappell; Susannah K. S. Thorpe (PLoS ONE, 2026)
Assessing the welfare of zoo-housed great apes is essential to ensure high standards of care, maintain zoos’ ethical and educational credibility, and support their conservation roles. However, welfare assessment remains challenging due to the complex cognitive, social, and behavioural needs of great apes and the limitations of existing evaluation methods. Many zoos rely on resource-based measures, which are easy to collect but lack the specificity needed to assess welfare accurately. In this study, we developed and tested a new standardized, evidence-based approach that integrated resource-based data with ecological and behavioural insights. This Ape Welfare Assessment, Resources and Ecology (AWARE) Tool was developed through collaboration with the Great Ape Welfare group (GAWg) and aimed to: (1) collect a holistic suite of resource and husbandry data that measures the constraints on the apes opportunities to express key naturalistic behaviours, (2) contextualize results within species-specific research on wild and captive great ape behavioural ecology and welfare, and (3) extend beyond existing zoo accreditation standards to support zoos aspirations for higher levels of welfare. Using data from zoo-housed chimpanzees, we tested whether this approach enhanced the validity of resource-based welfare assessments. Results demonstrate that the approach strengthens welfare evaluations and provides a more nuanced understanding of captive great ape wellbeing. We also propose a new validation framework for holistic welfare assessment tools such as this, where validating all individual indicators is neither feasible nor informative. Ultimately, we aim for the AWARE Tool to serve as a web-based resource for independent zoo use and formal welfare assessments. Future research will expand its application to gorillas and orangutans. This study represents a major leap towards establishing robust, species-informed and validated welfare assessment methodologies for zoo-housed great apes.